Dissolution Kinetics of Metallic Silver using Ammonium Nitrate and Hydrogen Peroxide Solution as an Environmentally Friendly Cyanide Substitute - Aydogan, Salih; Abdelraheem, Mohamed Taha Osman; Ali, Babiker; Boyrazli, Mustafa (Shahrood Univ Technology, 2026)
This article describes the kinetics of utilizing ammonium nitrate to dissolve pure metallic silver in hydrogen peroxide solution (H2O2). Using pure metallic silver allows for precise leaching kinetics research by removing interference from impurities and facilitating accurate interpretation of rate-controlling mechanisms. The impact of temperature, rotation speed, H2O2 concentration, and ammonium nitrate concentration were all examined. The results show a favourable relationship between the rate of silver (Ag) dissolution and the rotation speed. Additionally, a low concentration of ammonium nitrate (between 0.003 and 0.20 M) has advantageous effects on Ag dissolution. The dissolution rate was significantly impacted by H2O2 concentrations between 0.08 and 0.15 M, because this range of H2O2 concentration required to provide sufficient oxidative potential for significant silver solubility. However, this effect is less pronounced in the 0.20-0.50 M range. 20-50 degrees C range of temperatures are advantageous since H2O2 is stable in this range. It was calculated that the activation energy was 25.66 kJ/mol.
Keywords: Ammonium nitrate; Hydrogen peroxide; Dissolution; Silver; Activation energy